Implementation of Pamsimas Policy in the Provision of Clean Water For the Community in Padang Pariaman District West Sumatra Province - Raharini, Hasmy; Frinaldi, Aldri (AMPLITUDO : Journal of Science and Technology Innovation, 2024)
Environmental management in harmony, harmony and balance with environmental functions is the embodiment of sustainable development. With the principles of good environmental governance, organizing government is more open (open government) so as to provide space for the community to participate. Pamsimas is a flagship program in the provision of drinking water and sanitation in rural/kelurahan areas to encourage an increase in the number of people who can access drinking water and sanitation services. The population growth in Padang Pariaman Regency in 2020 reached 430,626 people while in 2021 it reached 433,626 people. Where the population growth rate is 0.74%, illustrating the importance of providing clean water sources, especially by encouraging community involvement. Implementation of Pamsimas using a community-based approach means making the community the main actor and person in charge of implementing activities. The method used for the assessment is a literature study using secondary data. Participation of the community, government and various related parties can provide reinforcement and commitment so as to achieve the availability of water sources with an insight into sustainable development.